2013
DOI: 10.1590/s0100-204x2013000800024
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Crassostrea gasar cultured in marine and estuary environments in Brazilian waters

Abstract: -The objective of this work was to evaluate the growth of the mangrove oyster Crassostrea gasar cultured in marine and estuarine environments. Oysters were cultured for 11 months in a longline system in two study sites -São Francisco do Sul and Florianópolis -, in the state of Santa Catarina, Southern Brazil. Water chlorophyll-α concentration, temperature, and salinity were measured weekly. The oysters were measured monthly (shell size and weight gain) to assess growth. At the end of the culture period, the av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
23
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 14 publications
4
23
0
4
Order By: Relevance
“…Oysters from the present study showed a similar growth rate (5.8 mm and 6.6 g per month) compared to C. gasar oysters grown in shrimp ponds in the neighboring state of Rio Grande do Norte (5.2 mm per month) (DA SILVA et al, 2016). Moreover, the growth rate was better than oysters growing in shrimp ponds in the Sergipe state (2.37 mm per month) (ROSA, 2014) as well as in the marine and estuarine environments of South Brazil using spats produced in a hatchery facility (LOPES et al, 2013;PEREIRA et al, 2001). The latter authors reported oyster growth rates of 2.6 mm, 3.1 mm and 3.9 g per month.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oysters from the present study showed a similar growth rate (5.8 mm and 6.6 g per month) compared to C. gasar oysters grown in shrimp ponds in the neighboring state of Rio Grande do Norte (5.2 mm per month) (DA SILVA et al, 2016). Moreover, the growth rate was better than oysters growing in shrimp ponds in the Sergipe state (2.37 mm per month) (ROSA, 2014) as well as in the marine and estuarine environments of South Brazil using spats produced in a hatchery facility (LOPES et al, 2013;PEREIRA et al, 2001). The latter authors reported oyster growth rates of 2.6 mm, 3.1 mm and 3.9 g per month.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, some studies were conducted in order to evaluate oyster maturation (RAMOS et al, 2014), larval settlement (SILVEIRA et al, 2011) and performance in culture (LOPES et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…However, some efforts have been made by research institutions to understand certain biological aspects of C. gasar that may be useful in the production process (LOPES et al, 2013;RAMOS et al, 2014;SILVEIRA et al, 2011;GOMES et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In these ecosystems, the bivalves are used as food and a source of income for the local population. Such species are a promising economic alternative through a regular production system, as they grow fast (Lopes et al 2013) due to suitable temperatures (25-30°C) in the Northeastern region, in addition to the presence of an increasing consumer market.…”
Section: Introductionmentioning
confidence: 99%